Long-term Outcomes With Ifosfamide-based Hypofractionated Preoperative Chemoradiotherapy for Extremity Soft Tissue Sarcomas. (December 2018) - Pennington, Joseph Daniel; Eilber, Fritz C.; Eilber, Frederick R.; Singh, Arun S.; Reed, Jarred P.; Chmielowski, Bartosz; Eckardt, Jeffrey J.; Bukata, Susan V.; Bernthal, Nicholas M.; Federman, Noah; Nelson, Scott D.; Dry, Sarah M.; et al.
Abstract : Objectives: The objective of this study was to analyze outcomes for patients with soft tissue sarcoma of the extremities using neoadjuvant ifosfamide-based chemotherapy and hypofractionated reduced dose radiotherapy, followed by limb-sparing surgery. Materials and Methods: An Institutional Review Board (IRB)-approved retrospective review of patients treated at a single institution between 1990 and 2013 was performed. In total, 116 patients were identified who received neoadjuvant ifosfamide-based chemotherapy and 28 Gy in 8 fractions of preoperative radiation (equivalent dose in 2 Gray fractions, 31.5 Gy [α/β 10] 36.4 Gy [α/β 3]) followed by limb-sparing surgery. Local recurrence (LR), distant failure (DF), and overall survival (OS) were calculated. Univariate and multivariate analysis for LR, DF, and OS were performed using Cox analysis. Statistical significance was set at a P <0.05. Results: Median follow-up was 5.9 years (range, 0.3 to 24 y). Actuarial LR at 3/6 years was 11%/17%, DF at 3/6 years was 25%/35%, and OS at 3/6 years was 82%/67%. On multivariate analysis, only a positive surgical margin was significantly correlated with worse local control ( P =0.005; hazard ratio [HR], 18.33; 95% confidence interval (CI), 2.41- 139.34). Age over 60 years ( P =0.03; HR, 2.34; 95% CI, 1.10- 4.98) and tumor size over 10 cm compared with tumor size ⩽5 cm ( P =0.03; HR, 3.32; 95% CI, 1.15-9.61) were associated with worse OS. Conclusions: Soft tissue extremity sarcoma patients treated using reduced dose hypofractionated preoperative radiotherapy in combination with ifosfamide-based chemotherapy shows acceptable local control and warrants further investigation. Abstract : Supplemental Digital Content is available in the text.